NONRETROACTIVE PRINCIPLE FOR BUSINESS GUARANTEES IN EXISTING PLANTATION COMPANIES FOLLOWING THE CONSTITUTIONAL COURT DECISION NUMBER: 138/PUU-XIII/2015 - Roestamy, Martin; Sihotang, Sudiman; Giffari, Davi Aulia Indra (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study examines the legal implications of Constitutional Court Decision No. 138/PUU-XIII/2015 concerning palm oil plantation businesses in Indonesia, particularly regarding the requirement to obtain both a Plantation Business License (IUP) and Land Use Rights (HGU) cumulatively. While the decision was intended to ensure legal compliance, environmental accountability, and sustainable land governance, it has inadvertently created legal uncertainty for companies that had lawfully operated with only an IUP prior to the ruling. This has raised significant concerns about the retroactive application of legal norms and the risk of criminalizing actions that were previously considered lawful. By applying the principles of legal certainty, non-retroactivity, and justice within a democratic state governed by law, this research emphasizes the urgent need for transitional legal frameworks. These frameworks should aim to harmonize regulatory enforcement with investment protection, uphold the rule of law, and prevent arbitrary state actions. Ultimately, this study advocates for policy reforms that balance environmental objectives with the legal rights and economic security of legitimate business actors in the plantation sector